Pancreatic cancer‐secreted miR‐155 implicates in the conversion from normal fibroblasts to cancer‐associated fibroblasts. Issue 10 (30th September 2015) - Pang, Wenjing; Su, Jiaojiao; Wang, Yalei; Feng, Hui; Dai, Xin; Yuan, Yaozong; Chen, Xi; Yao, Weiyan
Abstract: Cancer‐associated fibroblasts (CAF) are a major constituent of the pancreatic cancer microenvironment and that the meaning is as intended. Pancreatic cancer cells can induce normal fibroblasts to convert into CAF and, reciprocally, CAF promote tumor invasions and proliferations. The mechanism of the conversion from normal fibroblasts (NF) to CAF remains unclear. MicroRNA are short non‐coding RNA involved in the post‐transcription gene regulation, which have been defined as an imperative controller in tumor invasions, proliferations and colony formations. Microvesicles (MV) have been proved to be an important mediator of intercellular communication and can selectively transport secreted microRNA from a donor cell into a recipient cell. In this study, we isolated primary pancreatic fibroblasts from wild type C57 mice and co‐cultured them with pancreatic cancer cell lines, BxPC‐3 and SW1990, and observed the conversion from NF to CAF, or at least CAF‐like cells. This phenomenon could also be replicated in primary fibroblasts treated with MV separated from a cancer cell media. We identified that miR‐155 was upregulated in PaC‐derived MV and we confirmed that normal fibroblasts could convert into CAF after MV containing miR‐155 had been taken up. TP53INP1 is a target of miR‐155 in fibroblasts and a downregulation of TP53INP1 protein levels could contribute to the fibroblasts' activation. These results indicated that pancreatic cancer cells might reprogram normal adjacent fibroblasts into CAF by means of secreted MV containing miR‐155. Targeting the circulating microRNA might be a potential therapy for malignant tumors. Abstract : In this study, we discovered that microvesicles, containing miR‐155, might be released by pancreatic cancer cells and incorporated by co‐cultivated primary fibroblasts. TP53INP1 might be a target gene of miR‐155 in fibroblasts, which may mediate proliferation and the activation of normal fibroblasts and to manifest the characteristics of cancer‐associated fibroblasts.